ANALISA SENGKETA DAGANG INDONESIA DENGAN UNI EROPA DALAM PERKARA NOMOR DS592 - Hidayat, Deden; Adiwibowo, Yusuf (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
This writing examines Case Number DS592 concerning the Nickel claim. This dispute involves Indonesia and the European Union. Trade settlement between Indonesia and the European Union has not yet reached its final point. Retaliation will be difficult to implement because developing countries are still very strong against developed countries. If we look at the case of Indonesia and the European Union in storing the DS592 number, it is possible that the European Union will retaliate against Indonesia for the losses it experienced in obtaining nickel. Based on the urgency that this case could disrupt the stability of international trade, the author will examine the principles, principles and regulations to come up with recommendations that can be used in resolving the settlement. The author concludes that steps that can be taken by Indonesia are to increase domestic competitiveness by increasing the scale of investment in the nickel downstream industry so that the domestic mining and mining materials processing industry will increase